Improvement of DNA extraction protocols for Nostochopsis spp. - Motham,M. (Chiang Mai University, 2015)
Nostochopsis spp. are a type of cyanobacteria which form mucilaginous balls. These cyanobacteria have a high content of polysaccharides, which makes it difficult to isolate their genomic DNA by the conventional method. In this research study, six protocols for improvement of DNA extraction from this cyanobacterium, including; crushing with glass beads and liquid nitrogen, washing with 3 M NaCl and crushing with glass beads, freezingthawing, crushing with glass beads and sonication, crushing with liquid nitrogen and adding polyvinylpolypyrrolidone (PVPP), as well as crushing with glass beads and adding lysozymes, were compared. It was found that, these protocols could improve both the quantity and quality of the extracted genomic DNA. Crushing with liquid nitrogen and adding polyvinylpolypyrrolidone was found to be most suitable for Nostochopsis spp. genomic DNA extraction. This method could provide the highest yield of the extracted genomic DNA. Moreover, the genomic DNA obtained was highly cleaned of the contaminated proteins and polysaccharides and it was found to be a high quality DNA template for PCR. In addition, this extraction method was also effective for other high polysaccharide content cyanobacteria, such as Nostoc commune and Phormidium sp.